ANTITERMITICIDAL EFFICACY OF PROPOLIS (APIS MELLIFERA) AGAINST HETEROTERMES INDICOLA (WASMANN) - Sonia Pervaiz; Ayesha Aihetasham; Nageen Hussain (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Termites are the most common eusocial insects which belongs to order Isoptera. Termites are the leading cause of wood decay in the natural environment. Most of the termite species cause economic damage. The major way of managing subterranean termites is to treat the soil with chemical insecticides near the active infestation. Excessive chemical compounds can pollute the environment due to high toxicity and low biodegradability. Propolis is a natural resinous material collected by honey bees (Apis mellifera) from various plant sources. These biologically active compound used to control subterranean termite, H. indicola (Wasmann). It is the most well-known alternative method used to control the infestation caused by H. indicola.Method: This study explored the efficacy of aqueous and ethanolic extracts of propolis of Apis mellifera against H. indicola. Preference index values of the both extract of propolis revealed their distinct repellent response against H. indicola.Results: Both propolis extracts exhibited repellent properties against H. indicola. The mean values of mortality were extremely varied at different concentration of both extract of propolis of A. merlifera. Conclusion: Both extracts of propolis were found repellent against H. indicola and also show maximum mortality at 30% concentration. Additionally, these extracts demonstrated notable insecticidal activity against H. indicola, underscoring its potential for use in pest control applications as a biologically.